STRENGTHENING THE LOCAL ECONOMY: MEASURING THE DIGITAL LITERACY OF UMKM TOWARDS THE EFFICIENCY OF ELECTRONIC TAX REPORTING - Hamdani, Muhammad Riko; Dura, Justita (Institut Teknologi dan Bisnis Asia Malang, 2024)
This study explores the level of digital literacy of Micro, Small and Medium Enterprises (SMEs) in Malang City and its impact on electronic tax reporting. Of the 99 SMEs operating for at least one year, the majority showed adequate digital literacy, with interest and skills in using electronic tax applications. A good level of digital literacy gives hope for the successful implementation of electronic taxes in Malang City. Data analysis shows that the readiness of digital literacy of SMEs significantly positively affects the obligation of electronic tax reporting. Increasing digital literacy can improve the efficiency of SME tax reporting, contribute to local economic growth, and ensure business continuity. Therefore, a deep understanding of digital literacy not only impacts SME operations but is also crucial to ensure good and sustainable tax compliance in the long term.